2007
DOI: 10.1016/j.amepre.2007.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Physicians and Their Smoking Knowledge, Attitudes, and Practices

Abstract: Background-China has the most smokers in the world. Physicians play a key role in smoking cessation but little is known about Chinese physicians and smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
133
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 36 publications
14
133
8
Order By: Relevance
“…The present study also revealed that few physicians set quit dates for their patients, which is in agreement with the findings of other studies. (15,21) In our study, the most common method of intervention was brief advice, which was reportedly given by 61.5% of physicians as a method of smoking cessation, a considerably lower proportion than the 95.8% reported in a study conducted in Canada. (22) The use of NRT by 2.8% was very low when compared with the 25% reported in Norway and the 95.8% reported in Canada.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The present study also revealed that few physicians set quit dates for their patients, which is in agreement with the findings of other studies. (15,21) In our study, the most common method of intervention was brief advice, which was reportedly given by 61.5% of physicians as a method of smoking cessation, a considerably lower proportion than the 95.8% reported in a study conducted in Canada. (22) The use of NRT by 2.8% was very low when compared with the 25% reported in Norway and the 95.8% reported in Canada.…”
Section: Discussioncontrasting
confidence: 42%
“…A significant proportion of physicians reported asking their patients about tobacco use, which is higher than the 44-48% reported in other studies. (15,21) However, only 39.4% asked their patients about the reasons for using tobacco. Failure to ask about the reasons for using tobacco denies physicians the opportunity of recommending the appropriate method of intervention, anticipating challenges during the stages of quitting and enlisting the necessary clinical and social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals' own behaviour and attitudes concerning healthy lifestyles have an influence on the counselling of patients. A recent survey in the USA reported ,6% tobacco use among healthcare professionals [1], while 41% of Chinese male medical doctors smoke [2]. Tobacco dependence treatment (TDT) efforts generally focus on physicians, but evidence suggests that physicians are inadequately trained to help smokers quit [3,4].…”
Section: To the Editorsmentioning
confidence: 99%
“…Of particular concern is the occurrence of multidrug-resistant (MDR)-TB with resistance to at least isoniazid and rifampicin, and extensively drug-resistant (XDR)-TB with additional resistance to any fluoroquinolone and at least one of the second-line injectable drugs, including kanamycin, amikacin and capreomycin. MDR-and XDR-TB need prolonged treatment duration, from 18 to 24 months after sputum culture conversion, as recommended by the World Health Organization (WHO) [2]. A prolonged duration of treatment may lead to poor adherence, higher cost and undue toxicity.…”
Section: To the Editorsmentioning
confidence: 99%